ASCORBATE PEROXIDASE6 delays the onset of age-dependent leaf senescence. Issue 2 (27th November 2020) - Chen, Changming; Galon, Yael; Rahmati Ishka, Maryam; Malihi, Shimrit; Shimanovsky, Vladislava; Twito, Shir; Rath, Abhishek; Vatamaniuk, Olena K; Miller, Gad
Abstract: Age-dependent changes in reactive oxygen species (ROS) levels are critical in leaf senescence. While H2 O2 -reducing enzymes such as catalases and cytosolic ASCORBATE PEROXIDASE1 (APX1) tightly control the oxidative load during senescence, their regulation and function are not specific to senescence. Previously, we identified the role of ASCORBATE PEROXIDASE6 (APX6) during seed maturation in Arabidopsis ( Arabidopsis thaliana ). Here, we show that APX6 is a bona fide senescence-associated gene. APX6 expression is specifically induced in aging leaves and in response to senescence-promoting stimuli such as abscisic acid (ABA), extended darkness, and osmotic stress. apx6 mutants showed early developmental senescence and increased sensitivity to dark stress. Reduced APX activity, increased H2 O2 level, and altered redox state of the ascorbate pool in mature pre-senescing green leaves of the apx6 mutants correlated with the early onset of senescence. Using transient expression assays in Nicotiana benthamiana leaves, we unraveled the age-dependent post-transcriptional regulation of APX6 . We then identified the coding sequence of APX6 as a potential target of miR398, which is a key regulator of copper redistribution. Furthermore, we showed that mutants of SQUAMOSA PROMOTER BINDING PROTEIN-LIKE7 (SPL7), the master regulator of copper homeostasis and miR398 expression, have a higher APX6 level compared with the wild type, which further increased under copper deficiency. Our study suggests that APX6 is a modulator of ROS/redox homeostasis and signaling in aging leaves that plays an important role in developmental- and stress-induced senescence programs. Abstract : The involvement of ASCORBATE PEROXIDASE6 in developmental and stress-induced leaf senescence is tightly regulated at the transcriptional and post-transcriptional levels.